Cell phone usage and academic performance: An experiment - Felisoni, Daniel Darghan; Godoi, Alexandra Strommer (Computers and education, 2018)
This paper makes use of an experiment to test the relationship between the actual average time students spend using their smartphones per day and academic performance. Differently from previous studies that rely on self-reporting mobile phone usage data, which tends to significantly underestimate the time spent by students at their phones, we employed Apps (namely ‘Moment’ and ‘App Usage Tracker’) to effectively measure actual usage. Collecting data from 43 students at Fundação Getúlio Vargas (FGV), a business school from São Paulo, Brazil, our analysis yielded a significant negative relationship between total time spent using smartphones and academic performance, after controlling for known predictors of performance such as self-efficacy and past academic results. Each 100 min spent using the device on average per day corresponded to a reduction in a student's position at the school's ranking of 6.3 points, in a range from 0 to nearly 100. Moreover, if we consider usage during class time only (as opposed to during free time and weekends), the effect was almost twice as high. The magnitude of the effect found is alarming. Thus, this study brings new evidence of the potential harm of excessive smartphone use and should be useful for educators and other academic stakeholders interested in the subject of the impact of technology on students' performance. •Evidence that excessive cellphone usage might be harming student's performance.•Cellphone usage was directly measured, instead of relying on self-reported data.•A high correlation between cellphone usage and academic performance is found.•Usage during class time has a higher impact.